Confluence of AI, machine, and deep learning in cyber forensics - Misra, Sanjay 1971-; Arumugam, Chamundeswari; Jaganathan, Suresh; Saraswathi, Shunmuganathan (IGI Global, Publisher of Timely Knowledge, 2021)
"The book provides original research about cyber forensics and its relationship to Artificial Intelligence (AI) and presents the results of research and case studies that advance the practice and understanding of cyber forensics methods and techniques to support efficient and effective investigations. It covers a variety of topics, including forensic analysis, cloud forensics, forensics storage, mobile device forensics, forensic reporting, forensics tools, and more" - Provided by publisher
Keywords: Computer crimes / Investigation; Artificial intelligence